Synchronized random bit sequences generation based on analog-digital hybrid electro-optic chaotic sources - Zhao, Zexi (2020)
A novel synchronized random bit sequences (SRBS) generation technique based on analog-digital hybrid electro csv sources is numerically demonstrated. This scheme is based on two analog-digital hybrid electro-optic chaotic sources. The output analog chaotic signals are utilized as seeds of the random bit generators (RBGs). Different from existing chaos-based schemes, the synchronization of analog waveform is achieved by transmitting binary digital bits between the RBGs. Then, RBGs generate SRBS with the synchronized analog chaotic signals after some postprocessing strategies. Since the system only transmits digital signals between the RBGs, the robustness of SRBS generation can be improved dramatically. Moreover, existing communication facilities are compatible with the proposed scheme. The results indicate that the system could generate SRBS at Gb/s rates with available components. Randomness and synchronization performance of SRBS are investigated by NIST-800 randomness tests and BER analysis.